Yield gap analysis in oil palm: Framework development and application in commercial operations in Southeast Asia. (February 2017) - Hoffmann, M.P.; Donough, C.R.; Cook, S.E.; Fisher, M.J.; Lim, C.H.; Lim, Y.L.; Cock, J.; Kam, S.P.; Mohanaraj, S.N.; Indrasuara, K.; Tittinutchanon, P.; Oberthür, T.
Abstract: Narrowing the gap between actual and attainable yields in existing oil palm plantations is perceived as a key to fulfill the growing global demand for vegetable oil. To assess the scope for intensification we need robust estimates of attainable yields, which has been so far rarely done for perennial crops. For this purpose, we evaluated the complexities associated with estimating yield gaps (YGs) in oil palm (i.e. carry-over effect and aging), and adapted the existing framework for YG studies in annual crops. Based on this framework, we analyzed YGs for four sites within oil palm plantations located in Sabah (Malaysia), Central Kalimantan and North Sumatra (Indonesia) using a unique commercial yield data set covering an area of 38, 300 ha. We assessed for each site at plantation scale water-limited potential yield using the PALMSIM simulation model, attainable yield determined by best performing blocks within the plantation as defined by 90th percentile of observed yields and actual yields (blocks representing the median yields). The water-limited potential yield did not differ very much; 35–39 t fresh fruit bunch (FFB) during the plateau phase, the most productive phase in the life time of a palm. This reflected the favorable environmental conditions found in many parts of Sumatra and Borneo for oil palm. Attainable yields were in the range of 26–31 t FFB/ha. The exploitable YG between attainable and actual yield ranged for the four sites from 5 to 7 t FFB/ha/year. For one site (Central Kalimantan), we assessed yield variability due to varying soil conditions at the block scale according to its dominant soil type. This suggested that they were indeed exploitable by management. If the plantation could close the gap between attainable and actual yield this could give about 21, 000 t/yr higher FFB. This indicated the large scope for intensification oil palm offers in many parts of insular Southeast Asia. Highlights: We present a revised yield gap framework for oil palm. Carry-over and age effects play major role for understanding yield dynamics in oil palm. Quantification of the yield gap for four sites in commercial oil palm plantations Large scope for increasing oil palm production by improved management